Economic development of India in the post-colonial period: main features, problems, evolution - Alexander Stefanovich Ivashchenko (Вестник Майкопского государственного технологического университета, 2023)
After the liberation of the countries of Asia and Africa from colonial and semi-colonial dependence in the second half of XX century, they faced a whole series of problems that required urgent solutions. One of these problems was the task of ﬁlling the declared sovereignty with real eﬀorts to create capable, established states. Not all countries of the Afro-Asian region, even today, have managed to solve this problem. However, among the third world countries there are also quite a few states that have succeeded. India can be such an example.A country with almost one and a half billion people, with a complex multi-confessional and multi-ethnic structure became the third largest economy in the world at the beginning of the 21st century. The purpose of the article is to clarify the prerequisites for the dynamic development of India since 1947 including civilizational ones, as well as to identify the main stages in the development of the Indian economy and its characteristic features, diﬀerences in economic development from other developing countries, and main problems and diﬃculties. The following methods of scientiﬁc research have been used in the research: a comparative-and historical one, periodization method, problem and chronological method, historical and genetic method, etc.